Numerical Investigation of Wave Induced Scour Depth Around Slender and Grouped Monopile - Sürücü, Bekir; Bayraktar Bural, Deniz (Periodica Polytechnica Budapest University of Technology and Economics, 2025)
Wave-induced scour around monopile foundations poses a critical challenge for offshore wind turbine design, affecting stability, serviceability, and maintenance costs. Despite extensive experimental studies, high-fidelity numerical tools are still needed to capture complex interactions between wave kinematics, sediment transport, and pile geometry. This study presents a numerical investigation of scour depth around slender monopiles under regular wave conditions. A validated three-dimensional CFD model (FLOW-3D) employing the Volume of Fluid method and RNG k–ε turbulence closure was used to simulate wave–structure–seabed interaction. Sediment transport was modeled using the Meyer–Peter and Müller bedload formulation and an advection–diffusion equation for suspended load. The influence of the Keulegan–Carpenter (KC) number was examined for KC = 8.8–24, covering inertia- and drag-dominated regimes. Results showed that higher KC values intensified vortex-induced sediment transport and scour, while lower KC values led to gradual development. A marked increase occurred beyond KC ≈ 14, indicating a regime shift in flow–sediment interaction. Grouped-cylinder cases at G/D = 1 and 2 showed that narrow spacing produced mutual sheltering and reduced scour, whereas wider spacing caused deeper localized erosion. Single monopile predictions matched experimental data and empirical formulas, demonstrating the model's predictive capability. These findings emphasize the strong KC dependence of scour and suggest that spacing ratios above G/D = 1.5 may help mitigate adverse group effects in array layouts under oscillatory wave forcing.